Ceramic Materials
By using glass-ceramic/silver composite materials of alkaline earth metal silicate and aluminosilicate glass-ceramic system in high-temperature electrochemical conversion device, the problem of chromium degradation and thermal expansion mismatch is solved, and high conductivity and machinery are achieved Stability, improves the efficiency and reliability of SOFC and SOEC.
Patent Information
- Application Number
- CN202080029392.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-03-11
- Filing Date
- 2020-03-11
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2040-03-11
AI Technical Summary
The interconnect material in the existing high-temperature electrochemical conversion device has chromium degradation problems, resulting in reduced efficiency and insufficient mechanical stability, and it is difficult to match the thermal expansion coefficient of the ceramic electrolyte.
Using a breathable, conductive glass-ceramic/silver composite material based on alkaline earth metal silicate and alkaline earth metal aluminosilicate glass-ceramic system, by mixing silver-based particles with glass-ceramic precursor particles and sintering at specific temperatures , a glass-ceramic/silver composite material is formed without chromium to match the thermal expansion coefficient of the ceramic electrolyte and improve mechanical strength.
Achieve high conductivity and mechanical stability of glass-ceramic/silver composites without chromium under high temperature conditions, reduce chromium degradation and oxidation scale formation, match the thermal expansion coefficient of ceramic electrolytes, and improve the reliability of interconnects. Sex and efficiency.
Smart Images

Figure BDA0003306686560000141 
Figure BDA0003306686560000151 
Figure BDA0003306686560000161
Abstract
Description
Technical Field
[0001] The present invention relates generally to the field of glass-ceramic / silver composite materials and, in particular, to interconnect materials for high temperature electrochemical conversion devices such as solid oxide fuel cells (SOFCs) and solid oxide electrolysis cells (SOECs). It also relates to such devices incorporating glass-ceramic / silver composite interconnect materials. Background Art
[0002] Solid oxide fuel cells (SOFCs) are well-known devices that can oxidize fuels to generate electricity directly. Solid oxide electrolysis cells (SOECs) are related to SOFCs, but instead of generating electricity via fuel oxidation, they use electrical energy to produce hydrogen and oxygen via steam electrolysis. The individual cells in a SOFC stack (and SOEC stack) are connected in series, and each cell is separated from an adjacent cell by a conductive interconnect (referred to herein as an "interconnect"). The interconnect is typically a plate-like assembly that provides an airtight barrier between the anode of one cell and the cathode of an adjacent cell, and may have channels on either side to help distribute the individual gas streams to the appropriate electrodes. The interconnect material should be stable under both oxidizing and reducing conditions because it is exposed to the gas streams on the air side and the fuel side.
[0003] Interconnects made of ceramic (i.e., "ceramic interconnects") and interconnects made of metal (i.e., "metal interconnects") are known in the art. Interconnects can also be constructed from a mixture of ceramic and metal materials. With advances in materials, design, and battery manufacturing technology, there has been a general trend to reduce stack operating temperatures from 900°C-1000°C to between 600-750°C. This has allowed for wider use of metal interconnects, which are superior to ceramic interconnects due to mechanical strength, manufacturability, electrical conductivity, and cost, despite their poor chemical stability and poor thermal expansion match with other battery components. Metal interconnects are primarily made of high chromium ferrite alloys, such as 22APU (ThyssenKrupp, Germany) or chromium-based PM alloys, such as CFY (Plansee, Austria).
[0004] The presence of chromium in interconnect materials is beneficial because it has excellent resistance to oxidation atmospheres, but it has an adverse effect on the long-term performance of the stack. There are two main mechanisms by which chromium in metal interconnects causes performance losses in SOFCs. First, a chromium-based oxide scale forms on the air side of the interconnect. Although thin, this scale causes a significant increase in the resistance of the interconnect because the conductivity of the oxide is very low. At the operating temperature, the scale thickness increases over time, so the efficiency gradually but continuously decreases. Second, when exposed to a humid oxidizing atmosphere, chromium readily evaporates from the scale as volatile species such as CrO2(OH)2. The volatile chromium-containing species are easily transferred to the cathode, where they deposit and cause a severe loss of electrode efficiency (cathode poisoning) due to reduced catalytic activity. As the amount of chromium deposited during use increases, the cathode efficiency gradually decreases.
[0005] Different methods have been proposed to minimize or eliminate the problems associated with chromium in SOFCs, SOECs, and other high-temperature electrochemical reactors.
[0006] One approach is to coat the surface of chromium-containing metal interconnects. For example, US 5,942,349 proposes chromium-containing interconnects with a coating on the cathode side. The coating material contains at least one oxide selected from Mn, Fe, Co, and Ni, and this reacts with the chromium oxide on the surface of the interconnect to form a protective chromium-containing spinel layer. US 7,390,582 discloses a protective coating on a chromium-containing metal interconnect material having the following general formula: Co 3-x-y Cu x Mn y O4 (0 < x < 1.5, 0 < y < 3 and x + y < 3). The protective coatings disclosed in US 8,241,817 include rare earth oxide materials. US 8,366,972 describes a two-phase protective coating containing a Cu, Ni, Mn, Fe-based spinel phase and a second oxide phase containing Mn, Cu, and Ni. US 9,452,475 discloses a plasma-sprayed manganese cobalt oxide spinel protective coating on the air side of a SOFC interconnect. US 9,634,335 describes a composite perovskite / spinel coating for a chromium- and iron-containing interconnect material, whereby the coating is applied in the form of a powder mixture with a particle size less than 22 microns.
[0007] Generally speaking, the purpose of the coating on the interconnect is to provide a protective layer that has high conductivity and acts to block oxygen from diffusing from the surface of the interconnect to the underlying metal to reduce the rate of formation of a chromium-rich skin, and also provides a barrier for chromium to diffuse from the metal / skin interface to the surface of the interconnect to minimize the chromium evaporation rate. The rate of performance degradation can be significantly reduced, but the associated diffusion / evaporation process will not be completely stopped, so some long-term efficiency losses are inevitable. It is also reported (Goebel, C. et al. (2018) Journal of Power Sources, 383: 110-114) that the Cr2O3 layer always exists as an interface layer between the coating and the metal interconnect. Although this layer may be very thin, its extremely low conductivity means that no matter how high the conductivity of the coating material is, the area specific resistance (ASR) of the surface of the interconnect can never drop below a certain level.
[0008] In another case, as described in US 9,559,366, a chromium getter is used to capture the chromium from the gas phase to prevent it from poisoning the cathode.
[0009] Another approach is to use an interconnect that does not contain chromium. For example, US 7,396,384 and US 7,648,789 describe a SOFC interconnect having a sandwich structure in which a conductive interlayer is sandwiched between two thin ceramic plates. Each of the ceramic plates has a number of small perforations ("through holes") that are filled with a conductive material, thereby ensuring a continuous electrical path from one side of the interconnect to the other. The ceramic material is preferably zirconium oxide, as this provides a good expansion match with other cell components such as a YSZ electrolyte. The ceramic acts as an effective barrier to gas transport and also provides mechanical support for the conductive material. The conductive material is a silver-glass composite material typically containing 15wt%-30wt% glass. The glass phase is specified to be stable to crystallization, preferably having less than 40% crystallization by volume at the temperature and cooling rate used in the fuel cell. It is also specified that the glass composition should have only a small change in viscosity within the operating temperature range of the SOFC so that it can flow within the range and act as an effective seal, and it should preferably have a high silica content, such as 55wt%-80wt% SiO2 and a low coefficient of thermal expansion (CTE). An exemplary material contains 80wt% silver in a glass containing Na2O, K2O, CaO, BaO, B2O3, Al2O3 and SiO2.
[0010] An interconnect having a ceramic body with through holes is also described in US 6,183,897. The through holes are applied from the anode side and the cathode side, wherein the conductive filler material on the anode side has a CTE similar to the anode material, and the conductive filler material on the cathode side has a CTE similar to the cathode material. The anode side filler material and the cathode side filler material are in electrical contact within the thickness of the ceramic body to provide a continuous electrical path from one side of the interconnect to the other side. The materials suggested for the anode side and cathode side through hole filling are metallic materials such as silver-palladium, high chromium alloys, and lanthanum chromite doped with ceramic materials.
[0011] US 2005 / 0227134 discloses a SOFC interconnect having offset vias through at least two layers of a ceramic body. The conductive filler may be any suitable conductive material, such as strontium-doped lanthanum manganate (LSM), strontium-doped lanthanum chromite (LSC), or a metal, such as a silver-palladium alloy, a chromium oxide-forming metal, and / or platinum. It is suggested that if platinum is used as the conductive material, it may be combined with other conductive materials, such as silver and palladium alloys and / or with glass to reduce cost.
[0012] In all cases where conductive vias are proposed, the total surface cross-sectional area of the conductive material in the via is only a small fraction of the total area of the interconnect plate. For example, in US 7,396,384 and US 7,648,789, the total cross-sectional area of the via is described as 1000 mm2 per 1000 mm2. 2 Electrode contact area (on each side) 0.1 to 20 mm 2 This represents only 0.01%-2.0% of the interconnect plate area, resulting in severe reduction in through-thickness conductivity. In the preferred embodiments described in US 7,396,384 and US 7,648,789, 5400 mm 2 The coverage of the electrode contact area / gas separation region was limited to 19 vias with an average diameter of 300 μm (0.025% coverage, average via spacing of 15-20 mm). With such sparse via coverage, it is clear that these interconnect plates will need to be used in combination with current collectors on the electrodes or conductive coatings on the interconnect surfaces.
[0013] Another approach using vias is disclosed in US 6,051,330. In this case, the interconnect is made of cermets, including partially stabilized zirconia and superalloys resistant to oxidizing and reducing conditions. The metal content is above the percolation limit so that it provides a continuous conductive network from one side of the interconnect to the other. In this case, the vias are not filled with conductive material, but rather unfilled, as their function is to provide improved gas distribution.
[0014] US 2007 / 0037031 discloses an interconnect for a SOFC made of a cermet, wherein the cermet is electrically conductive and ionically non-conductive and ideally well matched in CTE to the SOFC electrolyte. The cermet is suggested to be made of any suitable conductive phase and any suitable ceramic phase. Many potential cermet compositions are postulated, but there is no evidence that these compositions can be manufactured, and no material property data for any cermet composition is disclosed. In particular, there is no demonstration that a good CTE match to a SOFC cell assembly can be achieved with the proposed cermet composition.
[0015] US 6,878,651 discloses a glass composition from the BaO-MgO-SiO2 system that can be used as a glassy matrix phase in a composite material employed in a ceramic electrolyte electrochemical converter device, primarily for sealing purposes. The glassy matrix phase is mixed with ceramic particles, such as forsterite (Mg2SiO4), and it is noted that the mixture can be sealed to a YSZ electrolyte at a temperature range of 1150°C-1200°C. It is suggested that metal particles, such as silver or ferritic stainless steel, be mixed with the glassy matrix phase, printed onto the electrode surface and fired at the sealing temperature to produce a conductive glass-metal coating that can be used as a cell-to-cell interconnect or current collector. However, the technical challenges associated with firing a silver-containing powder mixture at a temperature above the melting point of silver, about 200°C, are not addressed, particularly how to avoid dewetting and separation of the two phases.
[0016] There remains a need for alternative composite materials that can be used to form interconnects suitable for use in SOFCs, SOECs, or other high temperature electrochemical conversion devices. More specifically, there is a need for such materials that have properties that make them particularly suitable for use as interconnect materials in such devices and that can therefore be considered to represent an improvement over known composite materials. In particular, there is a need for composite materials that are substantially free of chromium and that may also have other advantageous properties, such as high electrical conductivity and a coefficient of thermal expansion that can be tuned to match a wide range of potential ceramic electrolyte materials.
[0017] The glass-ceramic / silver composites disclosed herein address these needs and provide a class of composite materials that are particularly suitable for use as conductive interconnects in SOFCs, SOECs, and other electrochemical conversion devices. Summary of the invention
[0018] The present inventors have now discovered that it is possible to produce gas-impermeable, electrically conductive glass-ceramic / silver composites (also referred to herein as "GC / Ag composites") based on a wide range of alkaline earth silicate and alkaline earth aluminosilicate glass-ceramic systems. As will be described herein, such composites have a number of advantages when used as interconnect components in electrochemical conversion devices, such as SOFCs and SOECs, when compared to currently employed interconnect materials.
[0019] In the description of composite materials, the terms "glass-ceramic / silver composite" and "GC / Ag composite" are used interchangeably herein and are intended to refer to a composite material containing a glass-ceramic and silver or a silver-based alloy. As used herein, the term "glass-ceramic precursor" is intended to refer to a glassy material that devitrifies upon heat treatment to form a glass-ceramic material.
[0020] From one aspect, the present invention provides a chromium-free glass-ceramic / silver composite precursor composition comprising:
[0021] Silver-based particles; and
[0022] Glass-ceramic precursor particles;
[0023] The composition comprises 30 wt % to 70 wt % of the silver-based particles, based on the combined weight of the silver-based particles and the glass-ceramic precursor particles.
[0024] In one embodiment, the glass-ceramic / silver composite precursor composition may be provided in the form of a homogeneous mixture or blend of the particles, such as in the form of a fine powder.
[0025] Glass-ceramic precursor particles can be prepared by the following method: wherein heating glass batch material to form a uniform melt, cooling it to form a precursor glass (e.g., in the form of glass frit), and grinding to form fine particles, such as powder. It should be understood that the cooling process is carried out in this way to avoid devitrification. The particles (e.g., powder) can then be combined with silver-based particles to form a glass-ceramic / silver composite precursor composition.
[0026] Viewed from another aspect, the present invention provides a chromium-free glass-ceramic / silver composite material comprising:
[0027] Silver-based phase; and
[0028] one or more crystalline ceramic phases;
[0029] The composite material comprises 30 wt% to 70 wt% of the silver-based phase, based on the combined weight of the silver-based phase, the one or more crystalline ceramic phases, and any residual glass phase.
[0030] Viewed from another aspect, the present invention provides a method of producing a glass-ceramic / silver composite material as described herein, the method comprising the steps of:
[0031] The glass-ceramic / silver composite precursor composition as described herein (e.g., an intimately mixed blend of glass-ceramic precursor particles and silver-based particles) is heated to a temperature above the glass transition temperature (T) of the glass-ceramic precursor composition. g) but below the melting point of the silver-based particles; and
[0032] The temperature is maintained within the range for a duration sufficient to effect sintering and crystallization of the glass-ceramic precursor composition.
[0033] Viewed from another aspect the invention provides a chromium free glass-ceramic / silver composite material obtainable or obtained by a process as herein described.
[0034] Viewed from another aspect, the present invention provides an interconnect for use in a high temperature electrochemical conversion device, wherein the interconnect comprises a glass-ceramic / silver composite material as described herein.
[0035] Viewed from another aspect, the present invention provides an electrochemical ceramic membrane reactor comprising at least two cells, each cell having an anode and a cathode, and having a gas-tight interconnection between the anode of one cell and the cathode of an adjacent cell, wherein the interconnection is formed from a glass-ceramic / silver composite material as described herein.
[0036] Viewed from another aspect, the invention provides the use of a glass-ceramic / silver composite as described herein as a gas-tight interconnect in a high temperature electrochemical conversion device, such as a solid oxide fuel cell (SOFC) or solid oxide electrolysis cell (SOEC).
[0037] The GC / Ag composites described herein are substantially free of chromium. This is a significant advantage because potential cell degradation mechanisms associated with chromium-containing metal interconnects (i.e., chromium poisoning of the cathode and formation of low-conductivity chromium oxide scale) are minimized and preferably avoided.
[0038] In one embodiment, the CTE of the composite materials disclosed herein can be finely tuned over a wide range by appropriate selection of the glass-ceramic composition and the silver content. For example, the CTE of the conductive GC / Ag composite materials described herein can be in the range of 8-15×10 -6 K -1 The CTE range of 25°C to 900°C allows for close matching of the CTE to a wide range of potential electrolyte materials. This is not the case with conventional ceramic or metal interconnect materials, as their coefficients of expansion are limited to a very narrow material-specific range. The ability to tailor the CTE for a variety of battery components enables significantly reduced residual stress levels during thermal cycling, which could greatly improve reliability.
[0039] In another embodiment, the GC / Ag composites of the present disclosure have high electrical conductivities. For example, these are comparable to, and in some cases higher than, ferrite and chromium-based alloys currently favored in device construction. More importantly, no oxide scale forms on the surface of the GC / Ag composites, so the gradual increase in area resistivity (ASR) seen during use of chromium-containing metal interconnects is significantly reduced and preferably, completely eliminated.
[0040] In another embodiment, the GC / Ag composites disclosed herein have better electrical performance than through-hole based interconnects known in the art because the volume fraction of the conductive phase is much higher. For example, the volume fraction of the conductive silver-based phase in the glass-ceramic / silver composites of the present invention is typically in the range of 23 volume %-40 volume %. In contrast, in the case of laminated, through-hole based interconnects, it is reported that the through-hole coverage does not exceed 2% of the surface area of the interconnect. Keeping in mind that the via fill material is a mixture of conductive (silver) and non-conductive (glass) materials, it is obvious that the volume fraction of the conductive phase in the outer (ceramic) layer of the through-hole based interconnect will be less than 2 volume %. Therefore, the ASR of the through-hole based interconnect will be much higher than that of the GC / Ag based interconnect described herein. In addition, the conductive phase is finely distributed on the surface of the GC / Ag composites described herein, thus directly achieving good electrical contact with the adjacent electrode. This is in stark contrast to the case of through-hole based interconnects because the through holes are small and widely separated on the surface of the interconnect, so that a conductive coating and / or current collector is required to achieve sufficient electrical contact with the electrode.
[0041] In another embodiment, the GC / Ag composite disclosed herein has the advantage of lower density when compared to conventional metal interconnects. The bulk density of the GC / Ag composite can be between 4.5-6.2 g / cm depending on the glass-ceramic system and the silver content. 3 Comparing this with the reported bulk density of CFY of 7.2 g / cm 3 and 7.7g / cm for ferrite alloy (Crofer / Sanergy) 3 The lower density leads to the potential for significant weight reduction of SOFC and SOEC stacks, which is particularly advantageous for non-stationary applications.
[0042] In at least some embodiments, the glass-ceramic / silver composites of the present disclosure have good mechanical strength, high Weibull modulus, and are expected to show relatively high toughness levels due to crack deflection and energy absorption processes in the continuous network of silver. As demonstrated herein, measurements made on glass-ceramic materials (without silver) show that these materials have excellent refractoriness, with expansion softening temperatures above 1000° C. Good creep resistance at high temperatures is expected due to the mechanical stability imparted by the continuous glass-ceramic skeleton in the GC / Ag composites.
[0043] In yet another embodiment, another advantage of the GC / Ag composite materials disclosed herein is ease of component manufacturing. The precursor powder mixtures from which these are formed can be processed using a wide range of standard ceramic processing techniques, such as tape casting, pressing, injection molding, etc., and can simply be heat treated in air, unlike known chromium-based CFY interconnect materials that require a protective atmosphere during manufacturing. This greatly simplifies the manufacturing process and also reduces its cost.
[0044] the term
[0045] As used herein, the term "glass batch" refers to a simple blend of components (eg, metal oxides, metal carbonates, etc.) that are not melt processed to form a precursor glass.
[0046] The glass batch is heated to form a "glass melt" and then cooled (e.g., by quenching) to form a "precursor glass." The precursor glass is ground to form a "glass-ceramic precursor" in the form of particles, which is combined with silver-based particles to form a "glass-ceramic / silver composite precursor composition" as described herein. The glass-ceramic / silver composite precursor composition can be combined with various additives and formed into a predetermined shape, referred to herein as a "green body."
[0047] Where CTE values are given herein, the values relate to the average CTE value over the specified temperature range.
[0048] As used herein, the term "chromium-free" means that the glass-ceramic / silver composite precursor composition or the glass-ceramic / silver composite contains less than 1 wt % chromium, preferably less than 0.1 wt % chromium. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 Schematic diagram of an exploded view of the basic components of a SOFC stack of an 'anode support' according to an embodiment of the present invention, showing the arrangement of cathode (1), electrolyte (2), anode (3) and interconnect (4).
[0050] Figure 2Graphs showing log(viscosity) versus temperature for pre-sintered precursor glasses 538 and 595 during heating at 3°C / min.
[0051] Figure 3 Scanning electron micrographs of polished sections of glass-ceramic / silver composites (A) GC588 / 55AgV and (B) GC538 / 65AgV are shown, illustrating the distribution of silver (light phase) in the glass-ceramic matrix. DETAILED DESCRIPTION
[0052] The present invention relates to a ceramic membrane reactor suitable for use as, for example, Figure 1 Glass-ceramic / silver composite material for a hermetic electrical interconnect in an 'anode supported' SOFC stack as depicted. The present invention also relates to glass-ceramic / silver composite material precursor compositions that can be used to produce such composite materials.
[0053] Glass-ceramic / silver composite precursor composition
[0054] In one embodiment, the present invention is directed to a chromium-free glass-ceramic / silver composite precursor composition comprising:
[0055] Silver-based particles; and
[0056] Glass-ceramic precursor particles;
[0057] The composition comprises 30 wt % to 70 wt % of the silver-based particles, based on the combined weight of the silver-based particles and the glass-ceramic precursor particles.
[0058] The glass-ceramic / silver composite precursor composition contains no chromium. Typically, the composition contains less than about 1 wt%, preferably less than about 0.1 wt%, and more preferably less than about 0.05 wt% chromium. Preferably, the composition does not contain chromium greater than trace levels, and is therefore considered to be "substantially free" of any chromium.
[0059] The glass-ceramic / silver composite precursor composition can be prepared by combining glass-ceramic precursor particles and silver-based particles as explained in more detail below.
[0060] Generally, the glass-ceramic / silver composite precursor composition will be provided in the form of a mixture comprising an intimate blend of silver-based particles and glass-ceramic precursor particles. Preferably, it will be provided as a free-flowing powder.
[0061] Glass-ceramic precursor particles
[0062] The glass-ceramic precursor particles used as the component of glass-ceramic / silver composite material precursor composition can be prepared via the melt processing of glass batch.Glass batch can be a simple blend (such as obtained by dry mixing) of required metal oxide and non-metallic oxide.The property of these components is not particularly limited, but these components should be selected so that they provide the ceramic phase composition of expectation in final glass-ceramic.After glass batch melting and gained melt homogenization, the glass melt is cooled to form an amorphous solid, preferably in the form of glass frit.Then amorphous solid is pulverized (such as by grinding) to provide the glass-ceramic precursor powder of suitable particle size.
[0063] In certain embodiments, the alternative metal compound that is converted into the corresponding metal oxide during melt processing can be used to replace the metal oxide in the glass batch, such as metal carbonate, nitrate or phosphate. When using these alternative metal compounds, the appropriate amount of compound in the glass batch can be easily determined based on the desired amount of each metal oxide in the final glass-ceramic precursor composition. In essence, the same molar amount is needed. By way of example, the glass-ceramic precursor composition comprising 25mol%MgO, 25mol%CaO and 50mol%SiO can be made of 25mol%MgO, 25mol%CaCO and 50mol%SiO 2的 Glass batch preparation (per 100 g of glass: 18.6 g MgO, 46.6 g CaCO3 and 55.5 g SiO2).
[0064] It may be advantageous to use an alternative metal compound as a precursor to the desired metal oxide, since some metal oxides react with moisture or CO2 in the air over time and thereby change composition, which may result in inaccurate weighing of the appropriate amount of metal oxide. Precursor compounds that are more stable than the corresponding metal oxide during storage may be preferred. Suitable precursor compounds include those mentioned above, such as metal nitrates, carbonates or phosphates.
[0065] It will be appreciated that more complex compounds may also serve as sources of the desired metal ions, such as magnesium silicate compounds. The skilled artisan is familiar with the formulation of glass batches and the various compounds that may be used to prepare glass batches.
[0066] The glass batch of metal / non-metal oxide or more generally metal / non-metal compound can be used as powder blending and carry out the melting processing step.In the melting processing step, the glass batch (for example oxide and / or non-oxide compound or may be the blend of compound) is for example higher than 1200 ℃, as 1400 ℃-1650 ℃, preferably 1200 ℃ to 1800 ℃, especially melted at the temperature of 1450 ℃-1600 ℃ to form homogeneous glass melt.
[0067] Preferably, the glass batch is heated in a suitable container, such as a platinum crucible, to a temperature sufficient to produce a homogeneous melt (typically at 1400° C. to 1650° C.).
[0068] The glass melt is then cooled to room temperature. Ideally, the glass melt is cooled rapidly, preferably by quenching in water to produce a glass frit. Rapid cooling is preferred because it helps to suppress devitrification. Using a water quench is preferred because the resulting glass frit is easily ground to form a powder. Therefore, the cooled glass melt, ideally the glass frit, should be easily ground to produce a precursor glass powder.
[0069] The amorphous solid formed after cooling is preferably then comminuted, for example ground, to produce a glass-ceramic precursor in the form of a powder, preferably a free-flowing powder. Preferably, the average particle size of the powder is 1-100 μm (e.g. measured by laser diffraction), such as 2 to 75 μm, for example 2 to 50 μm.
[0070] Suitable glass-ceramic precursor compositions for the present invention can be based on a series of alkaline earth metal silicates and alkaline earth metal alumina-silicate systems. In one embodiment, the glass-ceramic precursor composition includes one or more of the following metal oxides: MgO, CaO, BaO, ZnO, Al2O3, La2O3, SiO2, ZrO2, and P2O5.
[0071] In certain embodiments, the glass-ceramic precursor composition comprises 35 mol% to 65 mol% SiO2. For example, it may comprise 40 mol% to 65 mol% SiO2, such as 40 mol% to 60 mol% SiO2.
[0072] In certain embodiments, the glass-ceramic precursor composition comprises 5 mol% to 30 mol% MgO. In other embodiments, the MgO content is 10 mol% to 30 mol%, such as 10 mol% to 25 mol%. However, the presence of MgO is not required.
[0073] In certain embodiments, the glass-ceramic precursor composition comprises 15 mol%-40 mol% CaO. In other embodiments, the amount of CaO is 20 mol%-40 mol%, such as 20 mol%-35 mol%. However, the presence of CaO is not required.
[0074] In certain embodiments, the glass-ceramic precursor composition comprises 5 mol% to 30 mol% BaO. However, the presence of BaO is not required.
[0075] In certain embodiments, the glass-ceramic precursor composition comprises 5 mol% to 10 mol% ZnO. However, the presence of ZnO is not required.
[0076] In certain embodiments, the glass-ceramic precursor composition comprises 5 mol% to 20 mol% Al2O3. However, the presence of Al2O3 is not required.
[0077] In certain embodiments, the glass-ceramic precursor composition comprises 1 mol% to 10 mol% La2O3. However, the presence of La2O3 is not required.
[0078] In certain embodiments, the glass-ceramic precursor composition comprises 1 mol% to 10 mol% ZrO2. However, the presence of ZrO2 is not required.
[0079] The glass-ceramic precursor composition used in the present invention may, for example, have a composition represented by the general formula xAO-yAl2O3-zSiO2, wherein "AO" represents an alkaline earth metal oxide or a mixture of alkaline earth metal oxides, and x, y and z represent the mol% of AO, Al2O3 and SiO2, respectively. The sum of x, y and z may, but does not necessarily, total 100 mol%. It is understood that
[0080] In the case where x+y+z=100 mol%, the glass-ceramic precursor composition consists of AO, Al2O3 and SiO2, or in the case where y is 0, it consists only of AO and SiO2. However, as explained herein, additional components (e.g., B2O3, La2O3, ZrO2, etc.) may be present in the composition, in which case the sum of x+y+z will be less than 100 mol%. Suitable alkaline earth metal oxides "AO" that may be present in the composition include MgO, CaO, BaO, SrO, and mixtures thereof. Preferably, "AO" will be selected from MgO, CaO, BaO, and mixtures of these oxides.
[0081] Preferred examples of suitable glass-ceramic precursor compositions include those having the general formula xAO-yAl2O3-zSiO2, wherein AO represents an alkaline earth metal oxide or a mixture of alkaline earth metal oxides, x = 30 mol%-60 mol%; y = 0 mol%-20 mol%; and z = 35 mol%-65 mol%. Preferred compositions are those wherein x = 35 mol%-55 mol%; y = 0 mol%-15 mol%; and z = 40 mol%-60 mol%.
[0082] In some embodiments, the glass-ceramic precursor composition may include B2O3 and / or P2O5. Although including low melting point oxides such as B2O3 and / or P2O5 in the glass composition can be a convenient way to reduce the sintering temperature and improve densification by delaying the onset of crystallization, the addition level should ideally be limited because B2O3 and P2O5 easily form volatile species under typical SOFC and SOEC process conditions, which can adversely affect other components in the electrochemical cell such as electrodes. In addition, these oxides can damage the high temperature mechanical stability of the glass-ceramic because they promote the retention of the glassy phase during thermal treatment. In one embodiment, the glass-ceramic precursor composition contains 5mol% or less, such as 2mol% or less of B2O3. In one embodiment, the glass-ceramic precursor composition contains 5mol% or less, such as 2mol% or less of P2O5.
[0083] In some embodiments, the glass-ceramic precursor composition comprises 5 mol % or less, such as 2 mol % or less, of alkali metal oxides. For example, it may be substantially free of any alkali metal oxides.
[0084] Formation of glass-ceramic / silver composite precursor compositions
[0085] The glass-ceramic / silver composite precursor composition is prepared by mixing the glass-ceramic precursor particles described herein with silver-based particles. The mixing is generally carried out with suitable processing aids known in the art, such as solvents, binders, dispersants, viscosity modifiers, etc., to facilitate the formation of a "green body".
[0086] In a typical procedure, the glass-ceramic / silver composite precursor powder is molded together with any desired processing aids to form a 'green body' of the desired geometry. Suitable methods include methods well known in the art, such as casting, pressing, injection molding, 3-D printing, gel casting, etc. Organic processing aids, such as binders and plasticizers, are usually added before molding to facilitate the molding operation and give the molded part sufficient green body strength to allow handling. The molding process may involve pressing in a suitable metal mold. Any (one or more) organic processing aids, if added, will burn out during the heating of the molded preform to the desired heat treatment temperature.
[0087] In some cases, it will be convenient to produce the glass-ceramic / silver composite in the form of a thin tape. In this case, tape casting can be advantageously employed in the production of a 'green body'. Where a slightly thicker planar component is required, lamination of several layers of green tape can be used prior to heat treatment to increase the thickness to the desired level.
[0088] In some embodiments, the silver-based particles are silver particles, i.e., particles consisting essentially of silver, or particles consisting of silver (i.e., pure silver). However, in other embodiments, the silver-based particles are silver alloy particles, such as silver-palladium alloy particles. In the case of using a silver alloy, the alloying elements should not cause a decrease in the liquidus, and the silver alloy should include at least 50 wt% silver.
[0089] In one embodiment, the glass-ceramic / silver composite precursor composition comprises 40 wt% to 70 wt% silver-based particles, based on the total amount of glass-ceramic precursor particles and silver-based particles. In some embodiments, 50 wt% to 70 wt% silver-based particles may be used. In some embodiments, 45 wt% to 70 wt%, 45 wt% to 65 wt%, or 45 wt% to 60 wt% silver-based particles may be used.
[0090] In one embodiment, the present invention provides a chromium-free glass-ceramic / silver composite precursor composition comprising:
[0091] 40 wt% - 70 wt% silver-based particles; and
[0092] 30 wt% - 60 wt% glass-ceramic precursor particles;
[0093] Wherein the wt % is relative to the combined amount of the silver-based particles and the glass-ceramic precursor particles. Such compositions may be provided in the form of a powder or a 'green body' as described herein.
[0094] In one embodiment, the present invention provides a chromium-free glass-ceramic / silver composite precursor composition comprising:
[0095] 40 wt% - 70 wt% silver-based particles; and
[0096] 30 wt% to 60 wt% glass-ceramic precursor particles containing silicon dioxide (SiO2) and a combination of two or more oxides selected from the group consisting of MgO, CaO, BaO, ZnO, Al2O3, La2O3, ZrO2, and P2O5;
[0097] Wherein the wt % is relative to the combined amount of the silver-based particles and the glass-ceramic precursor particles. Such compositions may be in the form of a powder or a 'green body' as described herein.
[0098] In some embodiments, the glass-ceramic precursor particles may be composed of SiO2, metal oxides, and non-metal oxides. In some embodiments of the present invention, the glass-ceramic precursor particles are composed only of SiO2 and metal oxides.
[0099] Preparation of glass-ceramic / silver composite materials
[0100] The present invention provides a method for producing a glass-ceramic / silver composite material, the method comprising the following steps:
[0101] The glass-ceramic / silver composite precursor composition as described herein is heated to a temperature above the glass transition temperature (T) of the glass-ceramic precursor composition. g ) but below the melting point of the silver-based particles; and
[0102] The temperature is maintained within the range for a duration sufficient to effect sintering and crystallization of the glass-ceramic precursor composition.
[0103] Initially, as the glass-ceramic / silver composite precursor composition is gradually heated to a temperature above the T g , the material begins to sinter. The glass-ceramic / silver composite precursor composition is densified primarily by a process of viscous sintering of the glass-ceramic precursor phase as the temperature increases. The glass-ceramic precursor phase should remain amorphous during sintering. The formation of the amorphous-crystalline ceramic phase occurs during crystallization, which should ideally be performed after sintering is complete. Sintering typically involves heating to a temperature 100°C or higher above the Tg of the glass-ceramic precursor composition, such as at least 800°C, or at least 850°C.
[0104] The entire process (including sintering, and then crystallizing the glass-ceramic precursor phase) generally involves heating the glass-ceramic / silver composite precursor composition at a rate of 1 to 20°C per minute, such as 1 to 10°C per minute, first, reaching a sintering temperature range, wherein densification is performed via the viscous sintering of the glass-ceramic precursor particles. As the temperature further increases, the glass-ceramic precursor phase crystallizes. Crystallization is generally nucleated on the surface of the forming agent of the glass-ceramic precursor powder particles. The temperature is generally maintained at a temperature within the crystallization range sufficient to ensure that the crystallization process is completed. A typical time period is 1 to 5 hours, but longer or shorter time periods can be used.
[0105] Maintaining a temperature above the T of the glass-ceramic precursor composition g and below the melting point of the silver-based particles. In some embodiments, the temperature is maintained in the range of 900°C-950°C, such as 925°C-940°C.
[0106] A glass-ceramic / silver composite material is developed based on the crystallization of a glass-ceramic precursor phase. The resulting glass-ceramic comprises one or more crystalline ceramic phases and may also contain a small volume fraction (e.g., <10 volume %) of a residual glassy phase. After the glass-ceramic precursor phase is crystallized, the dilatant softening temperature of the resulting glass-ceramic phase exceeds the crystallization temperature, preferably is higher than the melting point of the silver-based phase, and more preferably is higher than 1000°C.
[0107] The present invention provides a chromium-free glass-ceramic / silver composite material composition, comprising:
[0108] Silver-based phase; and
[0109] one or more crystalline ceramic phases;
[0110] wherein the composition comprises 30 wt% to 70 wt% of the silver-based phase, based on the combined weight of the silver-based phase, the one or more crystalline ceramic phases, and any residual glassy phase.
[0111] In the glass-ceramic / silver composites described herein, the silver-based phase and the (one or more) crystalline ceramic phases formed during the heat treatment exist as an interpenetrating network within the material. The distribution of the different phases (in two dimensions) is shown by way of example only in the cross section of the GC / Ag composite. Figure 3 A and 3B. As will be seen, the silver-based material is sufficiently "interconnected" to provide a composite material having excellent electrical conductivity throughout the composite, while the crystalline ceramic phase is sufficiently "interconnected" to impart the desired high temperature mechanical strength.
[0112] The glass-ceramic / silver composite materials described herein do not contain chromium. Specifically, the material contains less than about 1 wt%, preferably less than about 0.1 wt%, and more preferably less than about 0.05 wt% chromium. Preferably, the glass-ceramic / silver composite materials contain no more than trace amounts of chromium.
[0113] In one embodiment, the residual glass content of the glass-ceramic phase is less than 10% by volume of the glass-ceramic / silver composite material, preferably less than 5% by volume. In one embodiment, the residual glass content of the glass-ceramic phase is less than 5% by volume, preferably less than 2% by volume.
[0114] In one embodiment, the silver-based phase is present in an amount of 20 vol% or more, preferably 25 vol% or more.
[0115] The conductivity of the glass-ceramic / silver composite material may be 1000 S / cm at 600° C., preferably 2000 S / cm or more at 600° C., preferably 3000 S / cm or more at 600° C. A suitable range of conductivity at 600° C. is 1000-20000 S / cm, such as 1500-20000 S / cm or 1500-15000 S / cm.
[0116] Uses of glass-ceramic / silver composites
[0117] The glass-ceramic / silver composites described herein find particular application as gas-tight interconnects within high temperature electrochemical conversion devices. For example, these can be used as interconnects in fuel cells or electrochemical devices based on proton-conducting ceramic membranes. The interconnect must have mechanical and chemical stability. Unlike other contact layers (e.g., conductive coatings) in an electrochemical conversion device, the interconnect should be able to provide mechanical support, i.e., it serves as a structural component of the device.
[0118] Thus, the present invention provides an interconnect, such as a fuel cell interconnect, comprising a chromium-free glass-ceramic / silver composite as defined herein.
[0119] The interconnect may be formed by forming the glass-ceramic / silver composite precursor material (and any desired processing aids) into a 'green body' having a desired shape, optionally with the aid of compression. As discussed herein, the green body is heat treated to achieve crystallization. Compared to the method for forming other contact layers in an electrochemical conversion device, which involves applying a paste to an underlying substrate and firing the paste in situ to form a thin layer or track on the substrate, the interconnect will be formed as a separate component substantially independent of the other components of the device. The interconnect may contain, consist essentially of, or consist only of a glass-ceramic / silver composite. Preferably, the interconnect is formed only of the glass-ceramic / silver composite described herein.
[0120] The interconnect is via-free, i.e., the interconnect does not have a preformed via filled with a via filling material. One skilled in the art will appreciate that the silver phase is not a via filling material because it is distributed throughout the glass-ceramic phase, whereas in an interconnect with vias, the via filling material is only present in selected, defined regions of the ceramic phase.
[0121] It will be understood that the size and shape of the interconnect will depend on the configuration of the stack into which it is incorporated and that a person skilled in the art will be able to envision a suitable structure. Typical interconnects may be plate-like for electrochemical devices of planar geometry, and may be cylindrical / annular in the case of electrochemical devices based on tubular geometry. In some cases, the interconnect may contain channels and / or ribs on one or both sides to aid in the efficient distribution of reactants on the fuel side and air side surfaces of the interconnect. Such contours of the surface may be produced via machining of a substantially planar structure, or may be achieved by pressing and sintering the glass-ceramic / silver composite precursor material into a green body having a desired shape as described herein. Figure 1 Component (4) in illustrates an example of a suitable interconnect.
[0122] In another aspect, the present invention provides an electrochemical ceramic membrane reactor comprising at least two cells, each cell having an anode and a cathode, and a gas-tight interconnection between the anode of one cell and the cathode of an adjacent cell, wherein the interconnection is formed from a glass-ceramic / silver composite composition as described herein. For example, the reactor may be a SOFC or a SOEC. Figure 1 An illustrative SOFC stack is shown in , which is an exploded view of the basic components of an 'anode supported' SOFC stack, showing the arrangement of cathode (1), electrolyte (2), anode (3) and interconnect (4).
[0123] In one embodiment, a glass-ceramic / silver composite may provide an interconnect between the first cell and the second cell.The first and second cells may be based on yttria stabilized zirconia (YSZ) as the solid electrolyte material.
[0124] The CTE (20℃-1000℃) of YSZ is about 10.3×10 -6 K -1 . In order to achieve a good CTE match with YSZ, a glass-ceramic precursor must be selected that will crystallize to form a glass-ceramic with relatively low thermal expansion. The inventors have determined that the CTE of the glass-ceramic / silver composite can be tuned by adjusting the amount of the silver-based phase. In general, the CTE of the glass-ceramic phase is lower than the CTE of the silver-based phase, so for a given glass-ceramic composition, the greater the amount of silver-based phase, the higher the CTE of the glass-ceramic / silver composite. In principle, the lower the CTE of the crystallized glass phase, the more silver-based phase can be added while still maintaining a good CTE match with YSZ.
[0125] The glass-ceramic / silver composites described herein also find use as oxidation resistant, electrical feed-through materials for ceramic bodies, such as those made of alumina, zirconia toughened alumina (ZTA), or zirconia.
[0126] The invention will now be described with reference to the following non-limiting examples.
[0127] Examples
[0128] By way of example, a number of conductive glass-ceramic / silver composites ("GC / Ag composites") according to the present invention were prepared as listed below. The GC / Ag composites were made with glass-ceramic matrices from a range of different alkaline earth silicate and alkaline earth aluminosilicate systems. These were chosen to illustrate that composites can be produced from a variety of precursor glass compositions.
[0129] Preparation and characterization of glass-ceramic precursors
[0130] The compositions of the precursor glasses are presented in Table 1.
[0131] Table 1
[0132]
[0133] Glass batch materials sufficient to produce 800g of each glass are prepared by mixing high purity raw materials (such as magnesium carbonate, calcium carbonate and barium carbonate, zinc oxide, aluminum oxide, quartz, zirconium dihydrogen phosphate and ammonium dihydrogen phosphate) in appropriate proportions. In the temperature range of 1450 ℃-1600 ℃, the glass batch materials are melted in a platinum crucible of zirconium oxide grain stabilization (ZGS), and once homogenized, each melt is quenched in cold water to form a fragile glass material. A small piece of glass is also cast by each melt to provide a sample for expansion analysis. Glass rods are cast on preheated steel plates, quickly transferred to an annealing furnace at 750 ℃ and kept at this temperature for 30 minutes. Subsequently, the rod sample is cooled to room temperature at a speed of 3K / minute or less.
[0134] Average particle size (d 50 ) Precursor glass powders in the range of 20-30 μm were produced by grinding the glass frit in an alumina grinding jar using alumina grinding media.
[0135] The glass transition temperature (Tg) of the precursor glass was measured on annealed glass rod samples cast from each glass melt. The measurements were performed on samples 40-50 mm long in a horizontal axis dilatometer at 6 K / min.
[0136] Disc samples were prepared from each precursor glass powder for evaluating viscosity properties. 8 mm diameter × 1.5-2 mm thick disc samples were prepared by uniaxial pressing of a single glass powder in a cylindrical mold. A PVA-based temporary binder (Optapix PAF 46, Zschimmer & Schwarz, Lahnstein, Germany) was added to the glass powder to aid in pressing and improve the green strength of the disc. The pressed discs were heated to a temperature just sufficient to achieve more or less complete densification during the 15 minute dwell period. The actual temperature required was experimentally determined by measuring the sintering shrinkage of disc samples kept at different temperatures for 15 minutes. Typically, the temperature required for complete sintering within 15 minutes is higher than the T determined from expansion measurements of the glass rod. g High 90℃-110℃.
[0137] The viscosity of sintered glass samples was measured in a parallel plate viscometer at a heating rate of 3 K / min according to ASTM C1351M-96 (2012). When the sample is heated above the glass transition temperature, a decrease in viscosity is seen, as expected for a glassy material. However, at some point during continued heating, the viscosity reaches a minimum and is then observed to increase due to the formation of (one or more) crystalline phases. For illustration purposes, Figure 2 The viscosity versus temperature curves of two sintered precursor glass powders are shown in FIG. 1 . For the precursor glass materials of the present invention, it has been found that a viscosity below about 10 7 A transient minimum viscosity of 0.001 Pa·s is required to avoid open porosity in the conductive GC / Ag composite after heat treatment. It is also desirable to have a minimum viscosity at a temperature below the melting point of the silver or silver alloy used in the GC / Ag composite, as this will allow high crystallinity of the precursor glass phase to be achieved within a reasonable time frame at a tolerable heat treatment temperature.
[0138] Crystallized samples of the precursor glass were prepared for determination of thermal expansion properties and density. 50 mm diameter discs, about 6 mm thick, were produced by uniaxial pressing of precursor glass powders with 2 wt % PVA binder added. A load of about 10 tons was used to press the discs. The green discs were heated to 400°C in air at 2K / min to burn off the temporary binder, then heated to a temperature of 940°C at 5K / min and held for 1 hour. The samples were cooled to room temperature at 5K / min.
[0139] Density measurements were performed on the heat treated discs by the Archimedes method using water as the immersion medium. Rod samples 40-45 mm long were cut from the heat treated discs for thermal expansion measurements. Thermal expansion measurements were performed in air on a 1.5-inch (1.3-inch) 1.5-inch (2.5-inch) 1.5-inch (4.5 ... The measurements were performed on a horizontal axis dilatometer (Model 801L) during heating to 1000° C. using a heating rate of 3 K / min. The correction for the pushrod / holder expansion was performed using a sapphire reference material measured under the same conditions.
[0140] The measured property data of the precursor glasses and their respective glass-ceramics after crystallization are shown in Table 2.
[0141] Table 2
[0142]
[0143]
[0144] *During heating of the vitreous sintered powder compact at 3 K / min
[0145] §Crystallization heat treatment 940℃ / 1 hour
[0146] Preparation of glass-ceramic / silver composite materials
[0147] The glass-ceramic / silver composite material is produced by heat treating an intimate mixture of a glass-ceramic precursor powder and a silver powder. The silver powder used was grades AGP-V0180-4 and AGP-H3150-9 (C50) from Doduco Contacts and Refining, Pforzheim, Germany. The mean particle size (d 50 ) are in the range of 15-35 μm and 4-15 μm, respectively (manufacturer's data).
[0148] A powder mixture containing 35wt%-47.5wt% glass-ceramic precursor and 65wt%-52.5wt% silver is made from various glass-ceramic precursor powders and silver powders. The glass-ceramic precursor and silver powder are first thoroughly dry mixed, and then a binder (Optapix PAF 46, Zimmermann Chemie, Lahnstein, Germany) is mixed to produce a thick paste. After drying, the paste is crushed and sieved to obtain a powder suitable for pressing. Uniaxial pressing (10 tons) 50mm diameter × 5mm thick discs are used to provide samples for thermal expansion measurements; pressing (2 tons) 20mm diameter × 2mm thick discs are used to provide samples for conductivity measurement; and 20mm diameter × 1.6mm thick discs are pressed (4 tons) from selected materials to provide samples for measuring mechanical strength. Heat treatment of the disks included heating in a muffle furnace at 1.5 K / min in air to 400° C. to burn off the binder and then heating at 5 K / min to a holding temperature in the range of 925° C.-940° C. (hold time 1-2 hours).
[0149] Rod samples of approximately 45 mm × 4 mm × 5 mm were cut from larger disks for CTE measurements. Thermal expansion measurements were performed on a 300 mm diameter alumina push rod and holder ( The measurements were performed in air on a horizontal axis dilatometer (Model 801L). The measurements were performed in air during heating (3K / min) to 900°C and cooling (-3K / min or slower) to 40°C. The pushrod / holder expansion was corrected using a sapphire reference material measured under the same conditions.
[0150] Prior to taking the measurements, the flat surface of the conductivity sample was lightly conditioned by rubbing with a 400 grit (37 μm) diamond pad. The sample dimensions were approximately 18 mm diameter x 1.8 mm thick. Conductivity measurements were taken using a standard 4-point probe method (Van der Pauw technique) in air at 50°C intervals over the temperature range of 300°C-800°C.
[0151] Mechanical strength measurements were performed on selected GC / Ag composites at the National Physical Laboratory (NPL), Teddington, UK. Strength was measured in biaxial bending of 20 test pieces of each selected material. The test pieces were discs of approximately 18.5 mm in diameter by 1.5 mm thick. The surface of the discs was lightly trimmed by rubbing with a 400 grit (37 μm) diamond pad to remove any surface protrusions that may have been produced by the pressing or sintering process. A ring-to-ring test fixture (16 mm / 6 mm diameter) was used with a crosshead displacement rate of 0.2 mm / min.
[0152] Density measurements were performed by the Archimedean technique using water as the immersion medium. The volume fraction of silver in each composite was calculated from the silver weight percentage and the measured density. The porosity of the composite was calculated from the previously measured density of the glass-ceramic matrix material and the measured density of the GC / Ag composite. Therefore, the calculated porosity does not include any closed porosity that may be present in the glass-ceramic matrix sample.
[0153] The composition and heat treatment details of the GC / Ag composites are listed in Table 3. The density, thermal expansion and conductivity measurements of the GC / Ag composites are summarized in Table 4. The mechanical strength measurements of selected materials are listed in Table 5.
[0154] Table 3
[0155]
[0156] Table 4
[0157]
[0158] ND = Not Determined
[0159] Table 4 shows that the available coverage range of GC / Ag composites with high conductivity is 8 to 15×10 -6 K -1 This provides a major advantage in the application field of interconnect materials because it can tune the CTE to match various cell components, such as SOFC and SOEC.
[0160] Table 5
[0161]
[0162] Table 5 shows that the selected GC / Ag composites have good mechanical strength. More importantly, the strength is very uniform, with extremely high Weibull modulus in each case. This indicates that the material has excellent crack tolerance and can be expected to have high reliability in use. In the case of the GC588 / 65V composite, significant inelastic behavior is observed before reaching peak load.
Claims
1. A chromium-free glass-ceramic / silver composite precursor composition comprising: Silver-based particles; and With the general formula xAO-yAl 2 O 3 -zSiO 2 wherein AO represents an alkaline earth metal oxide or a mixture of alkaline earth metal oxides, and x, y and z represent AO, Al 2 O 3 and SiO 2 mol %, and wherein x = 35 mol %-55 mol %, y = 0 mol %-15 mol %, and z = 40 mol %-60 mol %; and wherein the glass-ceramic precursor particles contain 5 mol % or less of B 2 O 3 , 5 mol% or less P 2 O 5 and 2 mol % or less of an alkali metal oxide; The composition comprises 30 wt % to 70 wt % of the silver-based particles, based on the combined weight of the silver-based particles and the glass-ceramic precursor particles.
2. The composition according to claim 1, which is in the form of a powder.
3. The composition of claim 1 or 2, wherein the glass-ceramic precursor particles contain one or more of the following: MgO, CaO, BaO, SrO, ZnO, La 2 O 3 、ZrO 2 and P 2 O 5 or a mixture thereof.
4. The composition according to claim 1 or 2, comprising 40 wt% to 70 wt% of silver-based particles.
5. The composition according to claim 4, comprising 50 wt% to 70 wt% of silver-based particles.
6. The composition according to claim 1 or 2, wherein the silver-based particles are silver particles.
7. The composition of claim 1 or 2, wherein the silver-based particles are silver alloy particles.
8. The composition of claim 7, wherein the silver alloy particles are silver-palladium alloy particles.
9. The composition of claim 7, wherein the silver alloy particles comprise at least 50 wt % silver.
10. The composition of claim 1 or 2, wherein the glass-ceramic precursor particles contain 2 mol % or less of B 2 O 3 .
11. The composition of claim 1 or 2, wherein the glass-ceramic precursor particles contain 2 mol % or less of P 2 O 5 .
12. A chromium-free glass-ceramic / silver composite material comprising: Silver-based phase; and With the general formula xAO-yAl 2 O 3 -zSiO 2 wherein AO represents an alkaline earth metal oxide or a mixture of alkaline earth metal oxides, and x, y and z represent AO, Al 2 O 3 and SiO 2 mol% and wherein x = 35 mol%-55 mol%, y = 0 mol%-15 mol%, and z = 40 mol%-60 mol%; and wherein the material contains 5 mol% or less of B 2 O 3 , 5 mol% or less P 2 O 5 and 2 mol % or less of an alkali metal oxide; The composite material comprises 30 wt% to 70 wt% of the silver-based phase, based on the combined weight of the silver-based phase, the one or more crystalline ceramic phases, and any residual glass phase.
13. The composite material of claim 12, wherein the material comprises 40 wt% to 70 wt% of the silver-based phase.
14. The composite material of claim 13, wherein the material comprises 50 wt%-70 wt% of the silver-based phase.
15. A composite material according to any one of claims 12 to 14, wherein the one or more glass-ceramic phases in the material contain less than 10% by volume of residual glass phase.
16. The composite material of claim 15, wherein the one or more glass-ceramic phases in the material contain less than 5 volume % residual glass phase.
17. The composite material of claim 16, wherein the one or more glass-ceramic phases in the material contain less than 2 volume % residual glass phase.
18. The composite material according to claim 12 or 13, wherein the silver-based phase is present in an amount of 20 volume % or more of the composite material.
19. The composite material of claim 18, wherein the silver-based phase is present in an amount of 25 volume % or more of the composite material.
20. The composite material of claim 12 or 13, wherein the silver-based phase is a silver phase.
21. The composite material according to claim 12 or 13, wherein the silver-based phase is a silver alloy phase.
22. The composite material of claim 21, wherein the silver alloy phase is a silver-palladium alloy phase.
23. A method for producing a chromium-free glass-ceramic / silver composite material according to any one of claims 12 to 22, the method comprising the following steps: heating the chromium-free glass-ceramic / silver composite precursor composition according to any one of claims 1 to 11 to a temperature above the glass transition temperature of the glass-ceramic precursor particles but below the melting point of the silver-based particles; and The temperature is maintained in a range above the glass transition temperature of the glass-ceramic precursor particles but below the melting point of the silver-based particles for a duration sufficient to effect sintering and crystallization of the glass-ceramic precursor particles.
24. The method of claim 23, wherein during crystallization, the temperature is maintained in the range of 900°C to 950°C.
25. The method of claim 24, wherein during crystallization, the temperature is maintained in the range of 925°C to 940°C.
26. A chromium-free glass-ceramic / silver composite material obtained by the process according to any one of claims 23 to 25.
27. An interconnect for a high temperature electrochemical conversion device, wherein the interconnect comprises the glass-ceramic / silver composite material according to any one of claims 12 to 22 and 26.
28. An electrochemical ceramic membrane reactor comprising at least two cells, each of which has an anode and a cathode, and a gas-tight interconnection between the anode of one cell and the cathode of an adjacent cell, wherein the interconnection is formed by the glass-ceramic / silver composite material according to any one of claims 12 to 22 and 26.
29. The electrochemical ceramic membrane reactor according to claim 28, which is a solid oxide fuel cell or a solid oxide electrolysis cell.
30. Use of a chromium-free glass-ceramic / silver composite material according to any one of claims 12 to 22 and 26 as a gas-tight interconnect in a high temperature electrochemical converter device.
31. Use of a chromium-free glass-ceramic / silver composite material according to claim 30, wherein the device is a solid oxide fuel cell or a solid oxide electrolysis cell.
